Assessing potential impact of tsunami on Penang Island via TUNA-RP simulation (MATEMATIKA, 2017)
The Indian Ocean mega tsunami that occurred on 26 December 2004 resulted in the death of over 200,000 people worldwide, including 52 deaths in Penang Island, Malaysia. This rare but devastating tsunami highlights the vulnerability to future tsunamis for Malaysian coastal communities living in affected areas. To assess the potential impact of future tsunami, numerical tsunami models are used to project the maximum inundation distances and maximum runup heights along the affected coastal areas. In this paper, the in-house one-dimensional tsunami runup model codenamed TUNA-RP is enhanced and used to investigate the relations between the steepness of beach slope and tsunami impact, specifically inundation distance and runup height. The simulation results of TUNA-RP show that the inundation distances and runup heights decrease exponentially as the steepness of beach slope increases. Inundation distance and runup height at seven high-risk coastal areas in Penang Island, such as Teluk Bahang, Batu Feringghi and Tanjung Bungah, are presented in this paper to highlight risks and vulnerability. At certain locations along Penang beaches, a worst-case scenario may result in a tsunami with runup heights of 10 m which is highly dangerous, that might potentially take the lives of hundreds or thousands. Recognizing this vulnerability to tsunami risks for Penang, further research is essential for developing tsunami resilience in the face of this tsunami hazard.